Case report: Primary chronic calcaneal bursitis treated with subtotal bursectomy in a cat - Jeon, YoungJin; Lee, Haebeom; Roh, Yoonho; Kim, Daehyun; Jeong, Seong Mok; Jeong, Jaemin (Frontiers in Veterinary Science, 2022)
A 6-year-old, female spayed Bengal cat with a bodyweight of 6.4 kg was presented with swelling of the bilateral calcaneal region and weight-bearing hindlimb lameness with a 4-month history of unsuccessful conservative therapy. On orthopedic examination, a cyst-like mass around the calcaneal tendon was palpated. Palpating the mass and flexing the tarsal joint triggered pain. Through ultrasonography and magnetic resonance imaging, an inflamed or fluid-accumulated lesion was suspected around the calcaneal tendon, but there was no evidence of calcaneal tendonitis. Swollen calcaneal bursae were removed surgically. Histopathologic examination revealed fibrosis and an edematous feature. The cat was diagnosed with primary bilateral chronic calcaneal bursitis based on history, clinical signs, and diagnostic results. Hence, subtotal bursectomy was performed. At 4 weeks postoperatively, the cat had no pain around the tarsal joints and was ambulating normally. Radiographic and ultrasonographic exams revealed no recurrence of swelling or inflammation in the calcaneal region. Thirteen-month follow-up confirmed acceptable function and no relapse of clinical signs. The inflammation of calcaneal bursa alone can be the primary cause of hindlimb lameness in cats. A cat with hindlimb lameness and swelling on the calcaneal region should be assessed with the possibility of primary calcaneal bursitis. Subtotal calcaneal bursectomy can be considered as an effective treatment for primary chronic bursitis.